Failure of the dog culling strategy in controlling human visceral leishmaniasis in Brazil: A screening coverage issue? - Lucas Christian de Sousa-Paula; Lidiane Gomes da Silva; Kamila Gaudêncio da Silva Sales; Filipe Dantas-Torres (Public Library of Science (PLoS), 2019)
In the present study, we assessed the annual screening coverage (i.e., the percentage of dogs that are screened for anti-Leishmania antibodies annually) in the municipality of Sobral, Ceará state, Brazil. Data on the number of dogs screened during 2008-2017 (except 2010) were obtained from the Centre for Zoonoses Control of Sobral. The annual screening coverage during 2012-2017 was calculated. Data on human visceral leishmaniasis (VL) cases during 2008-2017 were compiled from the National Disease Notification System. Correlation analyses were performed to assess the correlation between canine and human data. During 2008-2017, 73,964 dogs (range, 0 to 13,980 dogs/year) were serologically screened and 2,833 (3.8%) were positive. The annual screening coverage during 2012-2017 ranged from 11.1% to 45.7%. There were no significant correlations between the number of dogs culled and the number of human VL cases, canine positivity and human VL incidence, number of dogs culled and human VL incidence, or between canine positivity and number of human VL cases. An inconsistent and relatively low annual screening coverage was found in the study area, with no dog being screened in 2010 due to the lack of serological tests. Our results highlight that many dogs potentially infected with Leishmania infantum have been virtually overlooked by public health workers in the study area, perhaps with a negative, yet underestimated, impact on the control of canine and human VL. Hence, the failure of the dog culling strategy in controlling human VL in Brazil may be due to the low screening coverage and low percentage of culled dogs, rather than the absence of associations between canine and human infections.